ChemInform Abstract: First 14‐Layer Twinned Hexagonal Perovskite Ba14Mn1.75Ta10.5O42: Atomic‐Scale Imaging of Cation Ordering. Issue 39 (September 2016) - Tao, Fengqiong; Genevois, Cecile; Lu, Fengqi; Kuang, Xiaojun; Porcher, Florence; Li, Liangju; Yang, Tao; Li, Wenbo; Zhou, Di; Allix, Mathieu
Abstract: Polycrystalline Ba14 Mn1.75 Ta10.5 O42 (BMT) is prepared by calcination of a stoichiometric mixture of BaCO3, MnCO3, and Ta2 O5 (Al2 O3 crucible, 1473 K, 8 h), pelletizing, and further firing in air (1773 K, 12‐24 h).